Clinical, Humanistic, and Economic Value of ‘Good ON-Time’ in Advanced Parkinson’s Disease: A Multinational Real-World Study - Joohi Jimenez-Shahed; Irene A. Malaty; Jean-Philippe Azulay; Ashwini Parab; Connie H. Yan; Prasanna L. Kandukuri; Pavnit Kukreja; Jorge Zamudio; Alexander Gillespie; Angelo Antonini (Neurology and Therapy)
Abstract Introduction In advanced Parkinson's disease (aPD), ‘ON-time’ indicates periods of better symptom control, with ‘good ON-time (GOT)’ indicating control without troublesome dyskinesia. Despite its importance, the impact of increased ‘GOT’ on aPD outcomes is understudied. This study aims to evaluate the clinical, humanistic, and economic value of incremental hourly increases in ‘GOT’ for people with aPD. Methods The study analyzed data from people with aPD across seven countries, using the Adelphi Parkinson's Disease Specific Program survey (2017–2020). ‘GOT’ (calculated from self-reported ON/OFF-time and the proportion of troublesome dyskinesia time) was normalized to a 16-h day. Outcomes included symptom control, medication use, falls, activities of daily living (ADLs), quality of life (QoL), and healthcare resource utilization (HRU). Regression models evaluated relationships between incremental ‘GOT’ hours and outcomes. Results Of 802 patients (mean [standard deviation; SD] age, 76.1 [8.9] years; male, 60.3%) included in the analysis, mean (SD) ‘GOT’ was 13.1 (2.7) hours/day. Hourly increases in ‘GOT’ were associated with lower likelihood of reporting uncontrolled motor (odds ratio [OR] 0.79; 95% confidence interval (CI) [0.62, 1.01]) and non-motor symptoms (OR 0.88; 95% CI [0.80, 0.96]), taking ≥ 2 PD medication classes (OR 0.91; 95% CI [0.86, 0.97]) and lower fall risk (incidence rate ratio 0.91; 95% CI [0.87, 0.95]). Hourly increases in ‘GOT’ were significantly associated with reduced humanistic burden (greater ADL independence, OR 1.19; 95% CI [1.04 1.37]) and improved QoL (for Parkinson’s Disease Questionnaire [PDQ]-39: coefficient − 1.49; 95% CI [− 2.46, − 0.52]) and with reduced economic burden, with annual total HRU cost-savings of $8602.24 (95% CI − $12,192.70 to $5011.77). Conclusions In this multi-country, real-world study of people with aPD, hourly increases in ‘GOT’ were associated with improved clinical outcomes, greater humanistic value, and reduced economic burden. Interventions that maximize improvement of ‘GOT’ should be considered for people with aPD adequately controlled on current therapy.